Antimicrobial susceptibilities of Chlamydia trachomatis isolated from the urethra and pharynx of Japanese males. Issue 8 (August 2017) - Kai, Seiji; Wada, Koichiro; Sadahira, Takuya; Araki, Motoo; Ishii, Ayano; Watanabe, Toyohiko; Monden, Koichi; Uno, Satoshi; Araki, Tohru; Nasu, Yasutomo
Abstract: Objectives: Sexually transmitted infections due to Chlamydia trachomatis ( C. trachomatis ) are a worldwide public health problem. The aim of this study was to investigate the drug susceptibilities of C. trachomatis strains isolated from the urethra and pharynx of Japanese males. Methods: Urethral and pharyngeal swabs were collected between 2013 and 2014 from Japanese males with urethritis. Using a McCoy cell line, 18 chlamydial strains were isolated from urethra in 18 patients and 7 from the pharynx in 7 of the 18 patients. The minimum inhibitory concentrations (MICs) of levofloxacin (LVFX) and azithromycin (AZM) were measured using the standard method of the Japanese Society of Chemotherapy. Results: The MICs of LVFX and AZM against urethral chlamydial strains were 0.125–0.5 μg/mL and 0.125–0.25 μg/mL, respectively. In pharyngeal strains, the MICs of LVFX and AZM were 0.125–0.25 μg/mL and 0.125–0.25 μg/mL, respectively. In 7 patients with chlamydial strains isolated from both the urethra and pharynx, the MICs of LVFX between these strains were identical in 3 of 6 patients (no growth was observed for one pharyngeal strain), while the MICs of AZM between these strains were identical in all 6 patients (not performed for one patient). Conclusions: Our data suggest that C. trachomatis strains isolated from the urethra and pharynx of Japanese males are susceptible to LVFX and AZM. Although measuring the MICs of chlamydial strains is labor intensive, it is a significant surveillance tool for treating chlamydial infections and preventing the spread of STIs.